Applications and activities : HVAC strategies for common building types. (CIBSE guide ;, 2016)
This chapter, B0 focuses on how different types of building and different activities within buildings influence the choice of system. Although this title covers the most common activities and types of building, more detailed design information is available for others in specialist guidance. The other chapters, B1 to B4, address issues relating to specific services. There are usually several possible design solutions to any situation, and the Guide does not attempt to be prescriptive but rather to highlight the strengths and weaknesses of different options.